PENGARUH PENDIDIKAN KESEHATAN SADARI DENGAN ALAT PERAGA DAN VIDEO TERHADAP PENGETAHUAN IBU - IBU PKK DI KELURAHAN SUKABUMI SELATAN JAKARTA BARAT TAHUN 2020 - Meidina Fajrin, (2021)
In 2017, the number of breast cancer cases in West Jakarta was 2.24% or as many as 291 women diagnosed with breast cancer. Low knowledge, as well as the provision of inaccurate information, causes women did not to make good prevention efforts. So that there are still cases of breast cancer every year. This study aims to determine the effect of BSE (Breast Self-Exam) health education with demonstration property and video on the knowledge of PKK women. This research method was Quasi Experiment with Two Group Pre-Post Test design. The research was hold by conducting health promotion directly using demonstration property and online using video. The research was hold in January 2021 in Sukabumi Selatan Sub-District, West Jakarta. The sampling technique used total sampling with a total sample of 80 PKK women. Data analysis in this study used the Man Whitney test. To see the media that most influence BSE related knowledge. The results showed that there were differences in the average knowledge after health education using demonstration property and video with a P-value of 0.002. Where the demonstration property more influence BSE knowledge with an average of 48.31%. There was a significant increase in the knowledge of PKK women about BSE after health education was carried out. The recommendation is that PKK women can seek information from various sources regarding breast cancer detection and have the willingness to do early detection of breast cancer as an effort to prevent breast cancer case finding.